Ab interno trabecular bypass surgery with Trabectome for open‐angle glaucoma - Hu, Kuang (Cochrane Database Syst Rev, 2021)
BACKGROUND: Glaucoma is the leading cause of irreversible blindness. Minimally invasive surgical techniques, such as ab interno trabecular bypass surgery, have been introduced to prevent glaucoma from progressing.   OBJECTIVES: In light of the potential benefits for people with open‐angle glaucoma and the widespread uptake of the technique, it is important to critically evaluate the evidence for whether treatment with ab interno trabecular bypass surgery with Trabectome is both efficacious and safe. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL; which contains the Cochrane Eyes and Vision Trials Register; 2020, Issue 7); Ovid MEDLINE; Ovid Embase; the ISRCTN registry; ClinicalTrials.gov and the WHO ICTRP. The date of the search was 17 July 2020. SELECTION CRITERIA: We searched for randomised controlled trials (RCTs) of ab interno trabecular bypass surgery with Trabectome compared to other surgical treatments (other minimally invasive glaucoma device techniques, trabeculectomy), laser treatment, or medical treatment. We also included trials in which these devices were combined with phacoemulsification compared to phacoemulsification in combination with other glaucoma surgery or alone. DATA COLLECTION AND ANALYSIS: We used the standard methodological procedures expected by Cochrane. Our primary outcome was proportion of participants who were medication‐free (not using eye drops). Secondary outcomes included mean change in intraocular pressure (IOP), proportion of participants who required further glaucoma surgery, mean change in quality of life, proportion of participants who achieved an IOP of 21 mmHg or less, 17 mmHg or less, or 14 mmHg or less and rate of visual field progression. Adverse effects were the proportion of participants experiencing intra‐ and postoperative complications. All outcomes were measured in the short term (6 to 18 months), medium term (18 to 36 months), and long term (36 months or longer). MAIN RESULTS: In this update, we included one RCT which had previously been identified as an ongoing study in our 2016 publication. This trial was a single‐centre, single‐surgeon RCT set in Canada with 19 participants. Participants were adults who had open‐angle glaucoma, open angles, and had inadequately controlled IOP that required surgical intervention. The study was terminated before the intended sample size was reached 'due to slow recruitment and increasing lack of clinical equipoise over time'. This reduced the power of the study to detect clinically important effects. We assessed the trial as being at high risk of attrition, reporting, and other potential sources of biases. The risks of performance and detection bias are unclear. The intervention group of 10 people had Trabectome ab interno trabeculotomy combined with cataract extraction (phaco‐AIT) and the comparator group of 9 people had trabeculectomy with mitomycin C combined with cataract extraction (phaco‐Trab), one of whom was lost to follow‐up. Seven of 10 participants in the phaco‐AIT group and 4 of 8 in the phaco‐Trab group were medication‐free (not using drops) at 12 months (odds ratio (OR) 2.33, 95% confidence interval (CI) 0.34 to 16.2; very low‐certainty evidence). At 12 months, the mean change in IOP was worse for phaco‐AIT than for phaco‐Trab, but this evidence was very uncertain (mean difference (MD) 3.70 mmHg, 95% CI ‐1.44 to 8.84; very low‐certainty evidence) in the phaco‐AIT group, as was the difference in the mean number of IOP‐lowering drops taken per day (MD ‐0.41, 95% CI ‐1.22 to 0.40; very low‐certainty evidence). Only one participant in the phaco‐AIT group required further glaucoma surgery. The study protocol declared that quality of life and visual field progression were measured, but they were not reported All 8 participants with complete data in the phaco‐Trab group and 8 of 10 in the phaco‐AIT had at least one early or late postoperative complication (e.g. day 1 IOP spike, hypotony, choroidal effusion, bleb leak or encapsulation, uveitis, or peripheral anterior synechiae). The evidence was very low‐certainty due to high risk of bias for several domains for this study and for large imprecision of all estimates. We also identified one ongoing study, identified from the International Clinical Trials Registry Platform (ICTRP): a multicentre, open, RCT comparing Trabectome to ab interno trabeculectomy using microhook. The study investigators plan to recruit 120 adults between 20 and 90 years of age. The primary outcome is duration of treatment success. Secondary outcomes include postoperative IOP, number of anti‐glaucoma medications, and adverse events. AUTHORS' CONCLUSIONS: There is currently no high‐quality evidence for the outcomes of ab interno trabecular bypass surgery with Trabectome for open‐angle glaucoma. Properly designed RCTs are needed to assess the long‐term efficacy and safety of this technique.